Scenario-based stochastic shelter location-allocation problem with vulnerabilities for disaster relief network design. (20th April 2022) - Hansuwa, Sweety; Mohan, Usha; Ganesan, Viswanath Kumar
We formulate the shelter location-allocation problem considering the vulnerability of the demand locations and their network connectivities with the shelter locations for disaster management's preparedness and response phase. We propose a scenario-based stochastic model that assigns the set of candidate locations evaluating operational, budgetary limitations, and service level expectations. The solution presents an evacuee-allocation plan considering the best collection of less vulnerable network connectivities between the demand areas and the shelter locations. We present a linear relaxation heuristic and compare the heuristic performance with the scenario-based formulation solved using CPLEX 12.8 optimisation solver for various problem sizes. We finally apply and solve the problem using real-life case data obtained during the major flooding event in and around the Chennai Metropolitan Development Area during 2015 to present our model's applicability and emergency response requirements. [Submitted: 12 November 2020; Accepted: 19 April 2021]